Numerical evaluation of separation efficiency in converging T-junction with slug flow - Pao, W. (Emerald Group Holdings Ltd., 2020)
Purpose: Excessive liquid carryover in T-junction presents a serious operational issue in offshore production platform. Slug flow and diameter ratio of T-junction are considered as two major factors causing liquid carryover. Regular and reduced T-junction are being used as partial phase separator but their efficiency is low. Converging T-junction with two distinct diameters (primary and secondary) in branch arm is used to improve the phase separation efficiency. The motivation is to combine specific feature of regular and reduced T-junction to increase separation efficiency of existing T-junction without involving too much operational workover. The purpose of this paper is to numerically evaluate the separation efficiency of a converging T-junction design. The present model and its methodology was validated with in-house experimental data for 3 inches diameter flow loop. Design/methodology/approach: The slug flow regime was simulated using incompressible Eulerian mixture model coupled with volume of fluid method to capture the dynamic gas-liquid interface. Findings: The analyses concluded that T-junction with primary-secondary branch arm diameters combination of 1.0-0.5 and 0.67-0.40 managed to achieve 95 per cent separation efficiency. The research also confirmed that over reduction of T-junction secondary diameter ratio below 0.2 will lead to decrease in separation efficiency. Research limitations/implications: The present research is limit to air/water two-phase flow but the general results should be applicable for wider application. Practical implications: The proposed design limited excessive workover and installation for current and existing T-junction. Hence, cutting down installation cost while improving the separation efficiency. Social implications: The present research resulted in higher separation efficiency, cutting down production down time and lead to operational cost saving. Originality/value: The present research proposes an original and new T-junction design that can increase phase separation efficiency to over 90 per cent. The finding also confirmed that there is a limitation whereby smaller diameter ratio T-junction does not always resulted in better separation. Â© 2019, Emerald Publishing Limited.